Cooking skills related to potential benefits for dietary behaviors and weight status among older Japanese men and women: a cross-sectional study from the JAGES - Yukako Tani; Takeo Fujiwara; Katsunori Kondo (BMC, 2020)
Abstract Background Poor cooking skills have been linked to unhealthy diets. However, limited research has examined associations of cooking skills with older adults' health outcomes. We examined whether cooking skills were associated with dietary behaviors and body weight among older people in Japan. Methods We used cross-sectional data from the 2016 Japan Gerontological Evaluation Study, a self-report, population-based questionnaire study of men (n = 9143) and women (n = 10,595) aged ≥65 years. The cooking skills scale, which comprises seven items with good reliability, was modified for use in Japan. We calculated adjusted relative risk ratios of unhealthy dietary behaviors (low frequency of home cooking, vegetable/fruit intake; high frequency of eating outside the home) using logistic or Poisson regression, and relative risk ratios of obesity and underweight using multinomial logistic regression. Results Women had higher levels of cooking skills, compared with men. Women with a moderate to low level of cooking skills were 3.35 (95% confidence interval [CI]: 2.87-3.92) times more likely to have a lower frequency of home cooking and 1.61 (95% CI: 1.36-1.91) times more likely to have a lower frequency of vegetable/fruit intake, compared with women with a high level of cooking skills. Men with a low level of cooking skills were 2.56 (95% CI: 2.36-2.77) times more likely to have a lower frequency of home cooking and 1.43 (95% CI: 1.06-1.92) times more likely to be underweight, compared with men with a high level of cooking skills. Among men in charge of meals, those with a low level of cooking skills were 7.85 (95% CI: 6.04-10.21) times more likely to have a lower frequency of home cooking, 2.28 (95% CI: 1.36-3.82) times more likely to have a higher frequency of eating outside the home, and 2.79 (95% CI: 1.45-5.36) times more likely to be underweight, compared with men with a high level of cooking skills. Cooking skills were unassociated with obesity. Conclusions A low level of cooking skills was associated with unhealthy dietary behaviors and underweight, especially among men in charge of meals. Research on improving cooking skills among older adults is needed.